Examination of the latent factor structure and construct validity of the stigma of suicide scale-short form. Issue 10 (26th November 2018) - L. Williams, Caitlin; Cero, Ian; Gauthier, Jami M.; K. Witte, Tracy
ABSTRACT: A major limitation of research on attitudes toward suicide is that most measures lack evidence of a stable factor structure. To investigate the structure of recently developed stigma of suicide scale-short form (SOSS-SF), we conducted an exploratory factor analysis in a sample of 499 undergraduates. Results revealed a three-factor structure: Stigma, Isolation/Depression, and Glorification/Normalization. We also identified good convergent and discriminant validity between the SOSS-SF and related constructs. In a separate sample of 570 undergraduates, a confirmatory factor analysis (CFA) demonstrated adequate fit for the three-factor model. In addition, a multiple-group CFA demonstrated invariance across gender.